Privata markägares syn på vindskadeförebyggande åtgärder - Petersen, Axel af (2006)
Wind and wind damage has become a hot subject because of the storm "Gudrun" in January 2005. The main purpose of this study was to establish how the land owners attitude toward preventive wind damage actions was changing immediately after they had been struck by a storm.